Analysis of structural effects on coloring mechanism of Ru celadon porcelain. Issue 4 (29th June 2020) - Chen, Yen‐Yu; Bai, Yi‐Wun; Wei, Wen‐Cheng J.
Abstract: The glazes in celadon are Ca‐Al‐Si‐O based glasses with a trace of Fe species doped as a coloring agent. The color of celadon is generated by a dual‐coloring mechanism of chemico‐compositional coloring by Fe species, and structural coloring by inhomogeneities. In order to identify the effects on the structural coloring mechanism, Fe doped Ca‐Al‐Si‐O glasses based on the composition of celadon were systematically synthesized by a thermal melting method to compare with that of the shard of ancient Ru‐ware. The results show that the as‐prepared glazes consisted of bubbles, crystalline precipitates, and dual‐phasic glass areas. The crystalline precipitates are mainly facet anorthite grains surrounded by Ca‐Al‐Si‐O glasses. Spinodal decomposition of the Ca‐Al‐Si‐O glasses was observed, whose morphologies are either a spherical or a worm‐like patterns. From the analysis of optical spectra, the intensities of wavelengths in the green (495‐570 nm), yellow (570‐590 nm), and orange (590‐620 nm) are in mixture hybrid. The dominant factor of the structural coloring might due to Rayleigh scattering by the nano‐textures of duel‐phasic glasses (50‐100 nm), which increases the blue opalescence. The spinodal decomposition of celadon porcelain after the anorthite grains precipitated was also identified in this study. Abstract : The dominant factor of structural coloring mechanism to enhance "blue sky" color of Ru celadon porcelain should be Rayleigh scattering by spinodal decomposed duel phasic glasses. The anorthite grains and bubbles in the glaze may enhance the Mie scattering, which enhances the milk white coloring. The microstructure comparison of the samples confirms the spinodal decomposition in the glass phase after precipitated anorthite grains.